Skin integrity and pressure ulcers [ (VEA Australia / New Zealand Pty Ltd, 2010)
At some point in their careers, most nurses and nursing assistants will care for patients at risk kof developing pressure ulcers. Pressure ulcers are distressing, debilitating and difficult to manage. Yet in many cases pressure ulcers are readily preventable. In this program we see how understanding the causes and staging of pressure ulcers can lead to improved management. We also determine the best ways to assess a patient's risk of developing them, and discuss preventative actions like correct positioning and terning, measures that can be taken to protect skin integrity, and early intervention and treatment options.